Peran Guru Kristen sebagai Agen Restorasi dan Rekonsiliasi dalam Mengembangkan Karakter Kristus pada Diri Remaja sebagai Bagian dari Proses Pengudusan [The Role of Christian Educator as Agent of Restoration and Reconciliation in Developing Christ-like Character in Adolescence as part of the Sanctification Process] - Novel Priyatna (Universitas Pelita Harapan, 2017)
Sanctification is a process of maturation to becoming more Christ-like in character after a person experiences regeneration. In the context of adolescent faith development, apart from parents and church clergy, regenerated adolescents also need support from Christian teachers as the agent of restoration in order to restore the image of God in themselves and as the agent of reconciliation in order to restore their relationship with God, others, and themselves all of which have been affected by sin. Christian teachers can function as role models for these adolescents both inside and outside classroom settings. One of the biggest barriers for adolescents to develop a more Christ-like character are their irrational beliefs that influence their thoughts and behaviors. This article will discuss the role of Christian teachers in helping adolescents to become more Christlike in character in their daily life. BAHASA INDONESIA ABSTRAK: Pengudusan merupakan suatu proses pendewasaan menuju karakter Kristus setelah seseorang mengalami kelahiran baru. Dalam konteks perkembangan iman remaja, selain dari peran orangtua dan pendeta, para remaja yang telah lahir baru membutuhkan dukungan guru Kristen sebagai agen pemulihan untuk memulihkan gambar dan rupa Allah dalam diri mereka dan agen pendamaian untuk memulihkan relasi mereka dengan Allah, sesama, dan diri sendiri yang telah rusak karena dosa. Guru Kristen memiliki peran sebagai teladan bagi para remaja baik didalam maupun diluar konteks kelas. Salah satu hambatan terbesar bagi remaja untuk memiliki dan menghidupi karakter Kristus adalah irrational beliefs mereka yang mempengaruhi pikiran dan perilaku mereka. Artikel ini akan membahas bagaimana peran guru-guru Kristen dalam menolong para remaja untuk memiliki dan menghidupi karakter Kristus dalam kehidupan mereka sehari-hari.